PTH-003 Clinical assessment is superior to pathological assessment in determining completeness of excision of malignant polyps from the Bowel Cancer Screening Programme. (23rd September 2015) - Doering, S; Cohen, P; Martin, J P; Hoare, J M; Smith, G V; Dawson, P M
Abstract : Introduction: The management of the early malignant colorectal polyp is controversial. Currently estimates of lymph node involvement rely on pathological staging. Despite the risk of surgical intervention, there is an increasing trend to treat these tumours aggressively. The introduction of the Bowel Cancer Screening Programme (BCSP) in 2006 has increased the incidence of early colorectal polyp cancers, making management of these lesions a common clinical problem. Methods: All malignant polyps reported to be completely excised endoscopically within the BCSP between the period 1 October 2007 to 31 October 2009 were identified. All were discussed in the local MDT and the decision to proceed to surgical resection was based on many factors, including pathological complete resection, Haggitt/Kikuchi level, as well as other high-risk features such as lymphovascular invasion and tumour budding. Those for which surgery was suggested were included in the study. The pathological assessment of completeness of excision was recorded, as well as the degree of differentiation of the tumour. Following surgery the presence of residual tumour within the resection specimen was recorded, as well as the total number of retrieved lymph nodes and the presence of lymph node tumour infiltration. Results: 14 malignant polyps were felt to have been completely endoscopically resected during 726 colonoscopies within the study dates. Nine were pedunculated (64%) and five sessile (36%). There were no endoscopic complications. Six polyps (43%) were assessed to be incompletely excised after pathological review, one was pedunculated (17%) and five sessile (83%). 11 cancers (79%) were moderately differentiated and three (21%) were poorly differentiated. No post-surgical specimens had residual tumour present and there were no involved lymph nodes (mean number harvested 18, range, 1–62). One patient had a post operative anastomotic leak but there were no post operative deaths. All the lesions removed were Dukes A stage and there has been no tumour recurrence to date, over a mean follow-up of 9.5 months. Conclusion: Although the follow-up is short, these data suggest that endoscopic resection may be a curative treatment for malignant polyps, thus avoiding subsequent surgery and possible complications. Endoscopic, rather than pathological, assessment of complete resection may be a more reliable predictor of residual tumour, particularly in sessile lesions. The surgical rates for these large flat lesions could potentially be reduced by greater uptake of Endoscopic Submucosal Dissection, but careful technique and visualisation following standard polypectomy may avoid this lengthy and high-risk endoscopic intervention.